PENGARUH IJTIHAD IMAM SYAFI’I TERHADAP PERAN AKAL DALAM PEMBENTUKAN HUKUM ISLAM - Imam Syafi’i; Abdul Aziz (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
Abstract Imam Shafi'i positions human reason in the Istimbat al-Ahkam as a mediation of the 'Aqliyah proposition to reveal the purpose of God in the form of Nash, which sometimes has a relative nature (Dhahir, Mujmal, 'Aam, Mutlaq Etc.) where the mujtahid exploits his mind to reveal Nash's goal is to be grounded. That is in accordance with human expectations on this earth